Development of SUMADAYA HTML5-Based Learning Media to Improve Science and Social Studies Learning Outcomes for Fourth-Grade Elementary Students - Ana Shuhbatul Husnia; Galih Mahardika Christian Putra (Journal of Innovation and Research in Primary Education, 2026)
Despite constructivist pedagogical ideals, elementary science and social studies (IPAS) instruction remains predominantly teacher-centered with minimal technology integration and absent local wisdom contextualization, evidenced by 69% of students failing to meet learning achievement criteria. Employing ADDIE-based Research and Development methodology, this study developed and evaluated SUMADAYA HTML5-based learning media featuring culturally-inspired interactive galleries and traditional Sunda Manda game-inspired layouts. Twenty-six fourth-grade students participated in small-scale (n=6) and large-scale (n=20) trials. Mixed-methods data collection encompassed expert validation (media and content specialists), implementation observations, and pre-post achievement assessments, analyzed through Shapiro-Wilk normality tests, paired sample t-tests, and N-gain effect size calculations. Expert validation yielded 95% feasibility scores across technical and pedagogical dimensions. Paired sample t-tests confirmed statistically significant pre-post differences (p=0.00). N-gain analyses revealed moderate effectiveness (small group: 0.614; large group: 0.659), with large-scale implementation demonstrating slightly higher improvement, suggesting scalability potential. Results affirm Vygotskian social constructivist principles, wherein culturally-grounded technological scaffolding facilitates knowledge construction within proximal development zones. Moderate rather than high effectiveness reflects authentic constructivist learning processes requiring sustained engagement for deep conceptual mastery.